Adhesive for flexible copper-clad plate as well as preparation method and application of adhesive

By using adhesives composed of polyester resin, phenolic resin and epoxy resin, polyester resin is prepared by combining specific acids, alcohols and amines to prepare polyester resin, the poor heat resistance and short storage period of flexible copper clad adhesives are solved. Problem, achieving high temperature durability and long-term storage effects.

CN119391348APending Publication Date: 2025-02-07ZHONGHAN NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411748152.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing flexible copper clad adhesives have defects such as poor heat resistance, long curing time and short storage period.

Method used

Polyester resin is prepared by polyester resin, phenolic resin, coupling agent and epoxy resin, and polyester resin is prepared by formulating specific acids, alcohols and amines. The reaction of phenolic resin and epoxy resin is combined to achieve low temperature Curing and high temperature durability.

Benefits of technology

It realizes the advantages of adhesives such as high temperature resistance, good storage performance, high peel strength, and low low temperature reaction activity, can be stored at room temperature for a long time, and has the effect of energy-saving and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005164288260000091
    Figure BDA0005164288260000091
  • Figure BDA0005164288260000101
    Figure BDA0005164288260000101
  • Figure BDA0005164288260000102
    Figure BDA0005164288260000102
Patent Text Reader

Abstract

The invention provides an adhesive for a flexible copper-clad plate as well as a preparation method and application of the adhesive, and relates to the technical field of organic synthesis. Specifically, the adhesive comprises a first component and a second component, wherein the first component comprises 60-80 parts of polyester resin, 20-30 parts of phenolic resin, 0.5-1 part of a coupling agent and a plurality of solvents; the second component comprises epoxy resin; and the polyester resin is obtained by polycondensation of components including dibasic acid, dihydric alcohol, diamine, tribasic acid and trihydric alcohol. The adhesive disclosed by the invention can effectively overcome the defects of low heat resistance, long curing time, short storage period and the like of a conventional epoxy system; the adhesive disclosed by the invention has the advantages of low-temperature curing, high heat resistance, high toughness, high peel strength, long storage period and the like, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of organic synthesis, and in particular to an adhesive for a flexible copper-clad laminate, and a preparation method and application thereof. Background Art

[0002] Flexible copper clad laminate (FCCL) is a processing substrate material for flexible printed circuit boards (FPC), usually composed of a flexible insulating base film and metal foil. A flexible copper clad laminate composed of three different materials, copper foil, film, and adhesive, is called a three-layer flexible copper clad laminate (3L-FCCL), and a flexible copper clad laminate without adhesive is called a two-layer flexible copper clad laminate (2L-FCCL). Compared with rigid copper clad laminates, flexible copper clad laminates are thin, light, and flexible, and are widely used in electronic products such as mobile phones, televisions, and computers.

[0003] As the application of flexible copper clad laminates becomes more and more extensive, the performance requirements for related products are gradually increasing. Among them, the adhesives for three-layer flexible copper clad laminates mainly include polyester adhesives, acrylic adhesives, epoxy or modified epoxy adhesives, polyimide adhesives, phenolic-butyral adhesives, etc. The mainstream products on the market are composite products including epoxy resins and additives such as curing agents and toughening agents, but they also have defects such as low peel strength, high curing temperature, harsh storage conditions, and short service life.

[0004] Patent application CN109868102A discloses a modified epoxy resin adhesive for LCP-based flexible copper clad laminates and a preparation method, which includes epoxy resin and specific types of toughening agents, curing agents, promoters, surface additives and other additives, which can be prepared after high-temperature mixing; the adhesive can reduce costs, improve product bonding effects, and has high heat resistance and dimensional stability, but epoxy adhesives have high reactivity under promoter conditions, and have problems such as harsh storage conditions and short storage validity period.

[0005] Patent application CN109517538A discloses an adhesive for flexible copper clad laminates and a preparation method thereof. The adhesive is mixed with component A and component B. Component A includes: 50-60 parts of fluorine-containing elastomer polymer, 20-40 parts of epoxy resin, 40-80 parts of organic solvent, 5-10 parts of environmentally friendly flame retardant filler, 1.5-5 parts of impact modifier, 0.5-1 part of silane coupling agent and 0.1-1 part of reaction accelerator, and component B includes: 2-4 parts of curing agent and 2-10 parts of organic solvent. The adhesive has the advantages of low dielectric constant, high weather resistance, high bending resistance, higher stability and longer service life. However, it still has the problem of epoxy resin in storage.

[0006] Patent application CN117701201A discloses a high-temperature resistant lithium battery aluminum-plastic film inner layer adhesive, which is obtained by solution grafting modification using chlorinated polyolefin and polyolefin as raw materials in the presence of unsaturated acid, and has many advantages such as reasonable molecular weight distribution, stable application performance, good flexibility, excellent tensile strength, high temperature resistance, electrolyte resistance, strong adhesion and good impact resistance. However, epoxy phenolic requires high temperature curing without adding accelerators, which has high energy consumption and high temperature will accelerate the oxidation of the copper foil surface in the flexible copper clad laminate, thereby affecting the performance.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] The first purpose of the present invention is to provide an adhesive for a flexible copper clad laminate, which is mainly used to solve the defects of the adhesive in the application scenario of the flexible copper clad laminate, such as poor heat resistance, long curing time, and short storage cycle; the adhesive of the present invention can solve all the above defects while satisfying the bonding performance and mechanical properties.

[0009] The second object of the present invention is to provide a method for preparing the adhesive for flexible copper clad laminates, which is simple and easy to implement and can meet the needs of mass production.

[0010] A third object of the present invention is to provide a flexible copper clad laminate.

[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0012] An adhesive for a flexible copper-clad laminate, comprising a first component and a second component;

[0013] The first component includes the following components by weight: 60-80 parts of polyester resin, 20-30 parts of phenolic resin, 0.5-1 part of coupling agent, and some solvents; the second component includes epoxy resin;

[0014] The polyester resin is obtained by polycondensation of components including dibasic acid, diol, diamine, tribasic acid and triol.

[0015] A method for preparing an adhesive for a flexible copper-clad laminate comprises the following steps:

[0016] (1) a dibasic acid, a diamine and a catalyst are subjected to a first reaction until the amine value is less than 1 mgKOH / g; a diol and a triol are then added to conduct a second reaction until the acid value is less than 1 mgKOH / g; the reaction system is placed under vacuum conditions and heated to conduct a third reaction, and a triacid is added again and the reaction is continued to obtain a polyester resin;

[0017] (2) The polyester resin, phenolic resin, epoxy resin, coupling agent and solvent are fully mixed to obtain the adhesive.

[0018] A flexible copper-clad laminate comprises the adhesive for the flexible copper-clad laminate.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention provides an adhesive for flexible copper clad laminates, which has the advantages of good high temperature resistance, good storage performance, high peel strength, etc.; the adhesive of the present invention has low low-temperature reactivity and can be stored for a long time at room temperature (long storage period); compared with the traditional epoxy bonding system, it has a self-catalytic effect and can achieve low-temperature curing, avoiding the high reactivity and the effect of energy saving and environmental protection.

[0021] (2) The present invention provides a polyester resin for adhesive, which is prepared by polycondensation of a specific acid, alcohol and amine, and contains a certain proportion of polyamide structure and terminal carboxyl groups in its structure. Since the polyamide structure is in the polyester molecular chain segment, its activity is frozen at room temperature, so the storage conditions are low and the storage time at room temperature is greater than 60 days. Under high temperature conditions (>100°C), the chain segment activity is enhanced, and the -NH- on the amide group has nucleophilicity, which can attack the epoxy group with nucleophilicity to cause the epoxy group to open the ring. After the ring opening, the reaction activity with carboxyl and phenolic hydroxyl groups is higher, so it can promote the rapid reaction of the carboxyl groups of the epoxy resin and the polyester resin, and the epoxy resin and the phenolic resin, so that the adhesive as a whole has the advantages of low curing temperature, good heat resistance and high bonding strength. DETAILED DESCRIPTION

[0022] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but those skilled in the art will appreciate that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. Those who do not specify specific conditions in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. Those who do not specify the manufacturer for reagents or instruments used are conventional products that can be purchased commercially. In addition, terms "1", "2", "a", "b", etc. are only used for descriptive purposes and cannot be interpreted as indicating or implying relative importance.

[0023] A first aspect of the present invention is to provide an adhesive for a flexible copper clad laminate.

[0024] The adhesive comprises a first component and a second component; wherein the first component comprises the following components by weight: 60-80 parts of polyester resin, 20-30 parts of phenolic resin, 0.5-1 part of coupling agent, and a certain amount of solvent; the second component comprises epoxy resin; the polyester resin is obtained by polycondensation of components including dibasic acid, diol, diamine, tribasic acid and triol.

[0025] As a preferred embodiment, the mass ratio of the first component to the second component is 100:(20-30).

[0026] As a preferred embodiment, the mass fractions of each component in the first component include but are not limited to: polyester resin 60, 62, 65, 68, 70, 72, 75, 78, 80; phenolic resin 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30; coupling agent 0.5, 0.6, 0.7, 0.8, 0.9, 1; solvent 200, 225, 250, 275, 300, 325, 350, 375, 400; the units are dimensionless, and the mass fraction values ​​can be any point value listed above, or a numerical range formed by any two point values.

[0027] As a preferred embodiment, the polyester resin of the present invention is obtained by polycondensation of specific monomers, and specifically, the following monomer components are selected:

[0028] (a) the dibasic acid is a compound having ≤10 carbon atoms and containing two carboxyl groups, including but not limited to at least one of succinic acid, glutaric acid, adipic acid, terephthalic acid, isophthalic acid, sebacic acid or 1,4-cyclohexanedicarboxylic acid;

[0029] (b) the diol is a compound having ≤8 carbon atoms and containing two hydroxyl groups, including but not limited to at least one of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 2-butyl-2-ethyl-1,3-propylene glycol, 1,4-butanediol, pentanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, hexanediol or 1,4-cyclohexanedimethanol;

[0030] (c) the diamine comprises at least one of ethylenediamine, propylenediamine, butylenediamine, pentanediamine, hexamethylenediamine, decanediamine or phenylenediamine;

[0031] (d) the tribasic acid comprises at least one of trimellitic anhydride and trimesic acid;

[0032] (e) The triol includes at least one of glycerol and trimethylolpropane.

[0033] As a preferred embodiment, based on the amount of substance, the usage ratio of the dibasic acid, the diol, the diamine, the tribasic acid and the triol is (0.05-0.15): (0.45-0.55): (0.4-0.5): (0.005-0.01): (0.015-0.025).

[0034] As a preferred embodiment, the polyester resin includes one or more of the following characteristics: (A) an intrinsic viscosity of 0.6 dL / g to 0.8 dL / g; (B) an acid value of 10 mgKOH / g to 18 mgKOH / g; (C) a hydroxyl value of 2 mgKOH / g to 8 mgKOH / g; (D) a glass transition temperature of 10°C to 20°C; (E) a number average molecular weight of 20,000 g / mol to 30,000 g / mol.

[0035] As a preferred embodiment, the phenolic resin includes phenol type or bisphenol A type; in some optional embodiments, the phenolic resin is selected from one or more of Cytec PR515, PR371, PR899, PR5666, PR612, etc.

[0036] As a preferred embodiment, the epoxy resin includes bisphenol A type, bisphenol F type, phenolic type, and aliphatic epoxy; in some optional embodiments, the epoxy resin is selected from one or more including NPEL-128, NPEF-170, NPPN-631, CY179-1 or NPER-032.

[0037] As a preferred embodiment, the coupling agent is a silane coupling agent; those skilled in the art can select a conventional silane coupling agent available on the market.

[0038] As a preferred embodiment, the solvent includes at least one of butanone or toluene; in some more preferred embodiments, the solvent includes butanone and toluene in a mass ratio of 1:1.

[0039] As a preferred embodiment, the first component and / or the second component also include other functional auxiliary components, including but not limited to antioxidants, anti-ultraviolet agents, antioxidants, curing agents, flame retardants, toughening agents, modified fillers, catalysts, defoaming agents, etc.; those skilled in the art can arbitrarily and reasonably add auxiliary components according to the requirements of mechanical strength or reaction control, etc.

[0040] As a more preferred embodiment, the first component further includes a flame retardant filler, and the flame retardant filler includes at least one of magnesium hydroxide, aluminum hypophosphite, melamine cyanurate or biphenylpiperazine-1,4-substituted di(phosphite methyl ester). In some optional embodiments, the amount of the flame retardant filler is 20 to 30 parts by mass.

[0041] The second aspect of the present invention is to provide a method for preparing the adhesive as described in the first aspect. The preparation method mainly includes a preparation part of the polyester resin and a compounding part of the adhesive.

[0042] (1) Preparation of polyester resin: a dibasic acid, a diamine and a catalyst are reacted in a first reaction until the amine value is less than 1 mgKOH / g; a diol and a triol are then added to carry out a second reaction until the acid value is less than 1 mgKOH / g; the reaction system is placed under vacuum conditions and heated to carry out a third reaction, and a triacid is added again and the reaction is continued to obtain the polyester resin.

[0043] As a preferred embodiment, the temperature of the first reaction is 110°C to 140°C; the time of the first reaction is 20min to 40min. It can be understood that the reaction time provided in the present invention is for reference only, and the specific reaction limit here is based on the system amine value.

[0044] As a preferred embodiment, the first reaction and / or the second reaction are both carried out under an inert gas atmosphere, including but not limited to nitrogen, helium, neon, argon and other gas environments.

[0045] As a preferred embodiment, the temperature of the second reaction is 200°C to 240°C.

[0046] As a preferred embodiment, the temperature of the third reaction is 240°C to 260°C.

[0047] As a preferred embodiment, when the third reaction is carried out until the intrinsic viscosity of the reaction system is ≥0.6 dL / g, the tribasic acid is added.

[0048] As a preferred embodiment, after adding the tribasic acid, the reaction is continued for 8 to 20 minutes; it can be understood that the reaction time provided here is for reference only, and the specific reaction limit is based on whether the characteristic parameters such as the acid value, hydroxyl value, viscosity, etc. of the system reach the preferred characteristic values ​​of the polyester resin.

[0049] As a preferred embodiment, the preparation of the polyester resin can be carried out with the assistance of oscillation, stirring, shaking, centrifugation, ultrasound, etc., which helps to accelerate dispersion and obtain a relatively uniform dispersion system; in a more preferred embodiment, the first reaction, the second reaction and the third reaction are all carried out under stirring.

[0050] (2) Compounding of adhesive: the polyester resin, phenolic resin, coupling agent and solvent are fully mixed to obtain a first component; the first component and the second component are fully mixed to prepare the adhesive.

[0051] As a preferred embodiment, during the preparation of the first component, the polyester resin, the phenolic resin and the solvent are first stirred and mixed at 40° C. to 60° C. for 4 h to 8 h, and then the coupling agent is added and further mixed.

[0052] It is understandable that the first component and the second component used in the present invention can react under the action of a coupling agent, and thus can be packaged and stored independently in situations such as product storage or transportation, and the mixing process of the first component and the second component in the above step (2) can be carried out before use.

[0053] The third aspect of the present invention is to provide a flexible copper clad laminate; the flexible copper clad laminate comprises the adhesive as described in the first aspect.

[0054] It is understandable that the flexible copper clad laminate should also include a copper substrate and a film layer, and there should be corresponding material selection and preparation process, and the present invention does not impose any restrictions on them; when the flexible copper clad laminate adopts the adhesive of the present invention, whether or not other adhesive components are introduced, it can be regarded as an embodiment of the present invention.

[0055] As an optional implementation, the flexible copper clad laminate includes the following preparation method: firstly, the adhesive is coated on the film layer and dried, and then it is positioned and attached to the copper substrate, and then hot-pressed and cured to obtain the flexible copper clad laminate.

[0056] Example 1

[0057] (1) Preparation of polyester resin

[0058] S1: 0.1 mol of hexamethylenediamine, 0.5 mol of adipic acid and 2 g of tetrabutyl titanate were added to a reaction kettle, and the mixture was stirred and heated to 120° C. in a nitrogen atmosphere. The reaction was continued for 30 min until the amine value was less than 1 mgKOH / g, and then the reaction was terminated.

[0059] S2: Continue to add 0.45 mol of butanediol and 0.0075 mol of propylene glycol, stir in a nitrogen atmosphere, heat to 220° C. and react until the acid value is less than 1 mg KOH / g, and then terminate the reaction.

[0060] S3: The reactor was heated to 250°C and the reaction was continued under vacuum with stirring until the intrinsic viscosity of the reactant reached 0.6. Then, 0.02 mol of trimellitic anhydride was added and the reaction was continued with stirring for 10 minutes, and then the reaction reached the end point. At this time, the acid value of the resin product was 15 mgKOH / g, the hydroxyl value was 5 mgKOH / g, and the intrinsic viscosity was 0.7. Nitrogen was filled into the reactor and the vacuum was eliminated. The material was cut into pieces and discharged to obtain a polyester resin.

[0061] (2) Preparation of adhesive

[0062] S4: Weigh 70 parts of the polyester resin prepared in S3, 15 parts of the phenolic resin (PR899), and a solvent (butyl ethyl ketone: toluene = 1:1) that is 1.5 times the sum of the masses of the two, and stir and dissolve them at 50°C for 6 hours. After the resin is dissolved, add 0.6wt.% of a silane coupling agent, further mix evenly, filter out the kettle, and obtain a 40% cured adhesive component A.

[0063] S5: Epoxy resin (NPEL-128) was used as the adhesive B component, and the mixture was mixed at a mass ratio of A:B of 100:25 to prepare an adhesive.

[0064] Examples 2 to 13, Comparative Examples 1 to 12

[0065] The above example is basically the same as Example 1, with the only difference being that the amounts of the acid, alcohol and amine raw materials used in steps S1 to S3 are different, and the specific amounts are shown in Table 1 below; in addition, Table 1 also provides the chemical properties of the polyester resin prepared in S3, where Tg is the glass transition temperature, in °C; IV is the intrinsic viscosity, in dL / g; and the units of the acid value and the hydroxyl value are both mgKOH / g.

[0066] Table 1

[0067]

[0068]

[0069] Examples 14 to 20, Comparative Examples 13 to 18

[0070] The above example is basically the same as Example 1, the only difference is that the amounts of polyester resin, phenolic resin, epoxy resin and the type of epoxy resin are replaced in steps S4 to S5. The specific characteristics are shown in Table 2 below.

[0071] Table 2

[0072]

[0073]

[0074] Examples 21 to 25

[0075] The above example is basically the same as Example 1, with the only difference being that the types of acid, alcohol and amine compounds used in steps S1 to S3 are different from those in Example 1, and the specific usage values ​​are shown in Table 3 below; in addition, Table 3 also provides the chemical properties of the polyester resin prepared in S3, wherein Tg is the glass transition temperature, in °C; IV is the intrinsic viscosity, in dL / g; and the units of the acid value and the hydroxyl value are both mgKOH / g.

[0076] Table 3

[0077]

[0078] Test example

[0079] (I) The adhesives prepared in the above embodiments and comparative examples are respectively used for preparing flexible boards; the method is as follows: each adhesive is coated on the PI substrate by an automatic coating machine, and the dry adhesive amount is 20g / m 2 After coating, place it under 140℃ for 4 minutes for drying; after the dried film and copper foil are fixed, use a positive air fast press at 160℃ and 80kg / m 2 The pre-pressing was performed for 5 seconds and the pressing was performed for 2 minutes under the conditions; the pasted flexible board was then placed at 140°C for aging for 3 hours; the flexible boards corresponding to the adhesives were subjected to the following performance tests S1 to S3.

[0080] S1. Peel strength: refer to GB / T 8808-1988; cut the aged samples into 10 mm wide strips, and perform the peel strength test on a desktop tensile machine at a peeling angle of 180° and a peeling speed of 300 mm / min and record the results.

[0081] S2. Soldering resistance: Cut the matured samples into 50mm*50mm strips, bake them in a 120℃ oven for 10 minutes before testing, and then immerse them in a constant temperature solder liquid with a solder liquid temperature of 320±5℃. Each sample is immersed in tin for 10s and 3 times. After immersion in tin, take out the sample and observe whether there is stratification or blistering on the surface.

[0082] S3. High temperature long-term storage performance: Each flexible board was stored at 40° C. for 30 days, and then the performance tests of S1 to S3 were repeated and recorded.

[0083] (ii) The adhesives prepared in the above embodiments and comparative examples were tested for the amount of adhesive overflow. The method is as follows: Each adhesive was coated on the PI substrate by an automatic coating machine, and the dry adhesive amount was 20 g / m 2 After coating, it is placed at 140℃ for 4 minutes to dry to obtain a covering film with glue; the covering film is punched by a punching machine to obtain a covering film with a diameter of 50mm; it is then attached to an unused 70*70mm copper foil and laminated and pressed, and the image surveying instrument is used to measure and calibrate the amount of glue overflowing at the contact edge of the covering film and the copper foil and record it.

[0084] The results of the above test items are recorded as shown in Table 4.

[0085] Table 4

[0086]

[0087]

[0088] As shown in Table 4, the adhesive prepared according to the formula and process of the present invention has good high temperature performance and storage resistance performance in the actual application of flexible copper clad laminates, and can be cured at a relatively low temperature, and has good practicality.

[0089] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. An adhesive for a flexible copper-clad laminate, characterized in that: The adhesive comprises a first component and a second component; The first component includes the following components by weight: 60-80 parts of polyester resin, 20-30 parts of phenolic resin, 0.5-1 part of coupling agent, and some solvents; the second component includes epoxy resin; The polyester resin is obtained by polycondensation of components including dibasic acid, diol, diamine, tribasic acid and triol.

2. The adhesive for flexible copper clad laminate according to claim 1, characterized in that: The mass ratio of the first component to the second component is 100:(20-30).

3. The adhesive for flexible copper clad laminate according to claim 1, characterized in that: The polyester resin includes at least one of the following features: (A) intrinsic viscosity is 0.6 dL / g to 0.8 dL / g; (B) Acid value is 10 mgKOH / g to 18 mgKOH / g; (C) Hydroxyl value is 2 mgKOH / g to 8 mgKOH / g; (D) Glass transition temperature is 10℃~20℃; (E) The number average molecular weight is 20000 g / mol to 30000 g / mol.

4. The adhesive for flexible copper clad laminate according to claim 1, characterized in that: The monomer raw material of the polyester resin includes at least one of the following characteristics: (a) the dibasic acid comprises at least one of succinic acid, glutaric acid, adipic acid, terephthalic acid, isophthalic acid, sebacic acid or 1,4-cyclohexanedicarboxylic acid; (b) the diol comprises at least one of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 2-butyl-2-ethyl-1,3-propylene glycol, 1,4-butanediol, pentanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, hexanediol or 1,4-cyclohexanedimethanol; (c) the diamine comprises at least one of ethylenediamine, propylenediamine, butylenediamine, pentanediamine, hexamethylenediamine, decanediamine or phenylenediamine; (d) the tribasic acid comprises at least one of trimellitic anhydride and trimesic acid; (e) The triol includes at least one of glycerol and trimethylolpropane.

5. The adhesive for flexible copper clad laminate according to claim 1, characterized in that: Calculated by the amount of substance, the usage ratio of the dibasic acid, the diol, the diamine, the tribasic acid and the triol is (0.05-0.15): (0.45-0.55): (0.4-0.5): (0.005-0.01): (0.015-0.025).

6. The adhesive for flexible copper clad laminate according to claim 1, characterized in that: The first component also includes a flame retardant filler; The flame retardant filler comprises at least one of magnesium hydroxide, aluminum hypophosphite, melamine cyanurate or biphenylpiperazine-1,4-substituted di(phosphite methyl ester); Preferably, the amount of the flame retardant filler is 20 to 30 parts by mass.

7. The method for preparing an adhesive for a flexible copper clad laminate according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) a dibasic acid, a diamine and a catalyst are subjected to a first reaction until the amine value is less than 1 mgKOH / g; a diol and a triol are then added to conduct a second reaction until the acid value is less than 1 mgKOH / g; the reaction system is placed under vacuum conditions and heated to conduct a third reaction, and a triacid is added again and the reaction is continued to obtain a polyester resin; (2) The polyester resin, phenolic resin, epoxy resin, coupling agent and solvent are fully mixed to obtain the adhesive.

8. The method for preparing an adhesive for a flexible copper clad laminate according to claim 7, characterized in that: Step (1) includes at least one of the following features: (I) The temperature of the first reaction is 110°C to 140°C; (II) The temperature of the second reaction is 200°C to 240°C; (III) The temperature of the third reaction is 240°C to 260°C.

9. The method for preparing an adhesive for a flexible copper clad laminate according to claim 7, characterized in that: Step (2) comprises: First, the polyester resin, the phenolic resin and the solvent are stirred and mixed at 40° C. to 60° C. for 4 h to 8 h, and then the coupling agent and the epoxy resin are added in sequence and mixed evenly to obtain the adhesive.

10. A flexible copper-clad laminate, characterized in that: The invention comprises an adhesive for a flexible copper clad laminate as claimed in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Adhesive and preparation method thereof and soft copper-clad plate and preparation method thereof

    CN109517538A

  • Modified epoxy resin adhesive for LCP-based flexible copper clad laminate and preparation method and application

    CN109868102A

  • High-temperature-resistant lithium battery aluminum plastic film inner layer adhesive and preparation method thereof

    CN117701201A